Hyperspectral imaging reveals physiological changes associated with chilling injury in zucchini (Cucurbita pepo L.) during postharvest storage - Lucia Russo; Danial Fatchurrahman; Giuseppe Rosiello; Ayoub Fathi-Najafabadi; Maria Luisa Amodio; Giancarlo Colelli (Food Control, 2027)

Polyhexamethylene guanidine hydrochloride as active ingredient for anticariogenic products: studies in vitro and in vivo - Fernanda Gosuen Gonçalves Dias; Francielle Aparecida de Sousa; Rodrigo Cássio Sola Veneziani; Renato Luis Tame Parreira; Lucas de Freitas Pereira; Denise Crispim Tavares; Saulo Duarte Ozelin; Tábata Rodrigues Esperandim; Maria Anita Lemos Vasconcelos Ambrósio; Victória Marques Russo Ramos; Jhenice Palmeira Gallina; Isabela Rodrigues Caetano; et al. (Brazilian Journal of Microbiology, 2026)

Tetraselmis chuii: Valorization of dairy wastewater using lactose as an alternative carbon source to glucose/galactose - Gloria Sciuto; Salim Kichouh-Aiadi; Yolanda Soriano-Jerez; Cinzia L. Randazzo; Nunziatina Russo; Cinzia Caggia; Maria del Carmen Cerón-García; Asterio Sánchez-Mirón (Bioresource Technology, 2026)

Hyperammonaemic encephalopathy and subsequent arthritis due to Ureaplasma urealyticum in a haematopoietic cell transplant recipient: a case report and literature review - Claudia Bartalucci; Chiara Russo; Anna Maria Raiola; Massimiliano Gambella; Riccardo Varaldo; Carmen Di Grazia; Giulia Bartalucci; Marica Laurino; Emanuele Angelucci; Matteo Bassetti; Malgorzata Mikulska (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Isotopes, Genetic Markers and Microbiome: Tools for seafood traceability - Tomaso Patarnello; Alessandro Russo; Brina Pavlovič§; Marta Nerini; Massimiliano Marvasi; Aldo D’Alessandro; Barbara Cardazzo; Maria Elena Martino; Duccio Cavalieri; Nives Ogrinc (Reviews in Fisheries Science & Aquaculture, 2026)

Bathymetric distribution and co-occurrence of the gorgonians Eunicella cavolini and Paramuricea clavata in the Gulf of Naples (Italy, Mediterranean Sea) - Federica Ferrigno; Francesco Rendina; Rosalia Calicchio; Maria Luisa Pica; Giovanni Fulvio Russo; Roberto Sandulli; Luigia Donnarumma (Marine Biology, 2026)
Understanding the spatial distribution and ecological relationships of habitat-forming gorgonians is crucial for assessing the biodiversity and conservation status of Mediterranean coralligenous assemblages. This study investigates the distribution and co-occurrence patterns of the yellow gorgonian Eunicella cavolini and the red gorgonian Paramuricea clavata along the Gulf of Naples (Tyrrhenian Sea, Italy). Remotely operated vehicle surveys were conducted in 2018, 2021, and 2024 at depths between 30 and 100 m across 6 sites around Capri Island and Punta Campanella Peninsula. Bathymetric distribution, density and size of the colonies were analysed. Spatial differences were observed among sites, whereas no significant temporal differences were detected among years. The populations of E. cavolini exhibited a wider bathymetric distribution (30–100 m), while the P. clavata ones were mainly confined to deeper and more stable environments (> 50 m). The densities of E. cavolini were also higher (from 93 ± 29 colonies/100m 2 in 2018 to 105 ± 32 colonies/100m 2 in 2024) than P. clavata (from 47 ± 23 colonies/100m 2 in 2018 to 76 ± 46 colonies/100m 2 in 2024). The colony sizes of E. cavolini were smaller (22–25 cm) compared to the larger P. clavata (28–35 cm). Both species exhibited medium-to-small colony sizes compared to other studies, suggesting recent recruitment. Positive correlation between densities of these two species suggests shared environmental preferences and potential facilitative interactions rather than competitive exclusion, possibly indicating that their co-occurrence can have a stabilizing effect on the community structure, increasing habitat structural complexity and resistance to environmental stress. These results highlight the ecological importance of gorgonian forests in enhancing three-dimensionality and biodiversity of coralligenous habitats.

On the move: southern range expansion of Italian parti-coloured bats - Emiliano Mori; Leonardo Ancillotto; Mattia Falaschi; Orly Razgour; Mariella Baratti; Gianna Dondini; Simone Vergari; Andrea Viviano; Ivana Budinski; Marcello Consolo; Penelope Fialas; Renato Pontarini; et al. (Mammalian Biology, 2026)

An ATR-FTIR-Based Screening Strategy for Formulation–membrane Interactions and Invertebrate Oxidative Stress Signatures - Anamaria Mendonça Santos; José Adão Carvalho Nascimento Júnior; Cláudio Carvalho Santana Júnior; Ana Maria Santos Oliveira; Adriano Antunes de Souza Araújo; Laurent Picot; Izabel Almeida Alves; Mairim Russo Serafini (Journal of Pharmaceutical Innovation, 2026)

Performance of the SmartMe&You serious video games for home telemonitoring is related to cognitive status and resting-state electroencephalographic markers in healthy and Parkinson’s disease participants - Claudio Del Percio; Roberta Lizio; Mina De Bartolo; Matteo Carpi; Giuseppe Noce; Susanna Lopez; Antonio Pio Afragola; Federica Fiorentino; Filippo Carducci; Veronica Henao Isaza; Paolo Barone; Arianna Cappiello; et al. (GeroScience, 2026)
Unsupervised serious video games on the SmartMe&You home telemonitoring platform may enable the assessment of cognitive fluctuations in older individuals, with or without cognitive deficits. Here, we tested their validity in cognitively unimpaired older adults (Healthy) and patients with mild cognitive impairment and mild to moderate dementia due to Parkinson’s disease (PDCD). Such validity was assessed using Mini-Mental State Examination (MMSE) scores and resting-state eyes-closed electroencephalography (rsEEG) activity. Clinical, demographic, and rsEEG datasets were collected from 34 healthy and 68 PDCD participants. The SmartMe&You video games included 7 unsupervised cognitive tasks implemented on a commercial tablet. The rsEEG source activities in the individual delta, theta, and alpha frequency bands were estimated using the eLORETA freeware. As novel findings, we showed that game performance: (1) discriminated between healthy participants and PDCD patients, with overall accuracy exceeding 90%; (2) was positively associated with MMSE scores across all participants ( p < 0.00001); and (3) was negatively associated with global rsEEG source activity in the delta and theta frequency bands ( p < 0.00001). These findings suggest that serious videogames of the SmartMe&You home telemonitoring platform were feasible and sensitive to cognitive status across the spectrum from normal aging to Parkinson’s disease-related dementia. This approach provides a scalable, low-cost, and ecologically valid tool for remote cognitive monitoring, with future potential applications in both early detection and longitudinal tracking of cognitive decline.

Streamlined and green chromatographic approach for the determination of oxygen heterocyclic compounds in foodstuffs via miniaturised extraction - Elisa Irrera; Giovanna Cafeo; Marina Russo; Maria Luisa Calabrò; Luigi Mondello; Paola Dugo (Natural Product Research, 2026)

Thermal decomposition processes of a reconstituted cast-leaf tobacco: fate of nitrogen and carbon - Renata Migliaccio; Maria Maddalena Oliano; Francesca Cerciello; Carmela Russo; Barbara Apicella; Osvalda Senneca (Fuel, 2026)

First report of the production of palmarumycins and other secondary metabolites by Lasiodiplodia exigua from Retama raetam showing cankers and dieback - Maria Michela Salvatore; Carlo Bregant; Irene Russo Krauss; Marco Masi; Marina DellaGreca; Benedetto T. Linaldeddu; Anna Andolfi (Natural Product Research, 2026)

Fishing trawlers drive the fine-scale daytime distribution of bottlenose dolphins at the Tiber River estuary (Western Mediterranean Sea) - Maria Silvia Labriola; Antonio Parisi; Nadia Marinchel; Sofia Rinalduzzi; Alice Turchi; Giancarlo Giacomini; Daniela Silvia Pace; Tommaso Russo (Marine Environmental Research, 2026)

Antarctic threats: anthropogenic microfibers and plasticizers in the scallop Adamussium colbecki from the Ross Sea - Emma Ferrari; Maria Vittoria Barbieri; Roberta Russo; Aleix Balasch García; Valentina Ferrari; Silvia Simonetti; Giovanni Birarda; Lisa Vaccari; Elisa Bergami; Ethel Eljarrat; Ilaria Corsi (Environmental Research, 2026)

Serum concentrations of selenium, selenium species and metals in children newly diagnosed with leukemia: a hospital-based case-control study - Marco Vinceti; Teresa Urbano; Bernhard Michalke; Lauren A. Wise; Maria Caterina Putti; Eloise Pulvirenti; Claudia Favara; Silvia Di Federico; Federico Zagnoli; Giorgia Adani; Annadiletta Donà; Roberta Patti; et al. (Environmental Research, 2026)

Occurrence of oxazolidinone resistance genes in enterococci, staphylococci, and Mammaliicoccus sciuri from swine slaughterhouse wastewater, Italy - Francesca Romana Massacci; Serena Simoni; Elisa Albini; Maria Elena Nigro; Elisa Russo; Gloria D’achille; Claudia Paoletti; Gianluca Morroni; Marina Mingoia; Yao Zhu; Wanjiang Zhang; Carla Vignaroli; et al. (World Journal of Microbiology and Biotechnology, 2026)

Sensitivity analysis and surrogate modeling of a sulfur-driven autotrophic denitrification model - Andrea Trucchia; Grazia Guerriero; Alberto Tenore; Fabiana Russo; Maria Rosaria Mattei; Luigi Frunzo (Journal of Water Process Engineering, 2026)

Role of methyl jasmonate in enhancing pigmentation of Tarocco Sant'Alfio (Citrus sinensis [L.], Osbeck) oranges during cold storage - Alessio Allegra; Paolo Inglese; Giancarlo Colelli; Maria Luisa Amodio; Lucia Russo; Danial Fatchurrahman; Fernando Garrido-Auñón; Giuseppe Sortino; Giulia Modica; Laura Siracusa; Alberto Continella (Postharvest Biology and Technology, 2026)

Assessing flood hazards and evacuation safety in metro stations: insights from Paral·lel station (Barcelona) - Eduardo Martínez-Gomariz; Beniamino Russo; Maria Stefania Guadamud-Calderón; Jackson Téllez-Álvarez; Carlos H. Aparicio-Uribe; Edwar Forero-Ortiz (Natural Hazards, 2026)
The increasing frequency of extreme rainfall events due to climate change has heightened flood risks in underground transport systems. Metro stations, particularly concourses and staircases, are highly vulnerable, posing severe threats to passenger safety. This study assesses flood hazards in the Nou de la Rambla concourse of Paral·lel metro station (Barcelona) using a high-resolution two-dimensional hydraulic model developed with Iber software and calibrated with site-specific topographic data and historical observations. Four inflow scenarios (0.2, 0.4, 0.6 and 0.8 m 3 /s) were simulated to evaluate water depth, flow velocity, and evacuation feasibility based on three hazard indicators: specific force per unit width (SFPUW, M 0 ), critical velocity, and the depth–velocity product. The results indicate that flooding primarily affects station entrances and evacuation paths, where steep slopes and confined geometries amplify flow hazards. Pedestrian stability is especially compromised on access staircases and ramps. Hazard maps identify zones where pedestrian stability is most compromised, supporting targeted emergency response planning. This study advances previous research by applying human-centred flood hazard criteria in a real underground metro environment. The results underscore the importance of integrating hydraulic modelling with pedestrian safety assessment to support hazard-informed adaptation strategies for flood-resilient metro infrastructure.

Assessment of Bottom Trawl Impacts on the Status of Seabed Communities in European Seas - Jan Geert Hiddink; Sebastian Valanko; Luke Batts; Esther D. Beukhof; Mats Blomqvist; Stefan Bolam; Belén Calero; Michele Casini; Marina Delgado; Jochen Depestele; Joanna Desmidt; Gabriele Di Bona; et al. (Fish and Fisheries, 2026)
Bottom trawling affects seabed habitats, but its large‐scale impacts remain poorly quantified. Assessment of trawling impacts is essential to support monitoring and achieving sustainability objectives under international conventions, sustainable development goals, and seafood certification programs. We present a Europe‐wide quantitative assessment of bottom trawling impacts, accounting for regional seabed‐community sensitivity drivers, across the Baltic, Atlantic, Mediterranean and Black Sea continental shelves. Using two risk‐based indicators of seabed status—Relative Benthic Status determined as benthic community biomass relative to seabed fauna carrying capacity (RBS tot ) and RBS sen (biomass of the 10% most sensitive fauna relative to carrying capacity)—we found substantial regional and habitat differences. The Black, Baltic and Aegean‐Levantine Seas showed low trawling intensity and high seabed status across habitats. In contrast, the Western Mediterranean, Ionian and Central Mediterranean and Adriatic Seas were the most severely impacted. Trawling affected the sensitive species biomass fraction more strongly than the total community biomass. RBS tot was in good condition (here chosen as RBS > 75% for epifauna) for over 79% of habitat‐ecoregion combinations. In contrast, RBS sen met this threshold in only 46% of these. A strong correlation emerged between the mean trawling intensity and RBS tot and RBS sen , allowing the use of SAR to estimate ecosystem status. This relationship can support decisions on where, and by how much, SAR reductions are needed to achieve good environmental status in regions where no detailed assessment is available. Our approach provides a quantitative framework to balance fishery production with ecosystem sustainability, offering tools for environmental and fisheries management in Europe.

Rare earth elements in transitional ecosystems: preliminary data from the LTER Lagoon of Venice site (Italy) - Nicola Nurra; Stefania Squadrone; Alessandro Bergamasco; Ermelinda Del Buono; Edoardo Di Russo; Alessandra Griglione; Chiara Marchese; Maria Cesarina Abete; Elisa Camatti (Environmental Science and Pollution Research, 2026)

The unnatural selection: Plant evolution and adaptation in the Chernobyl and Fukushima Exclusion Zones - Gian Marco Ludovici; Paola Amelia Tassi; Alba Iannotti; Colomba Russo; Samuele Maria Giorgio; Andrea Malizia (Journal of Environmental Radioactivity, 2026)

Postbiotic Potential of Newly Isolated Riboflavin-Overproducing Lactiplantibacillus plantarum Strains - Angela Scauro; Maria Teresa Rocchetti; Mario Soccio; Barbara la Gatta; Maria Teresa Liberatore; Nicola De Simone; Giuseppe Spano; Daniela Fiocco; Pasquale Russo (Probiotics and Antimicrobial Proteins, 2026)
Lactic acid bacteria (LAB) are food-grade microorganisms able to produce and release bioactive compounds of interest to human health. Some LAB strains can synthesize vitamin B2, i.e., riboflavin, a micronutrient essential for cellular metabolism. In this work, six Lactiplantibacillus plantarum isolated from fruits of the Mediterranean area were exposed to the selective pressure of roseoflavin in order to select spontaneous riboflavin-overproducing phenotypes. The best strains, as determined by the level of riboflavin produced, were characterized for some basic probiotic features, including antibacterial activity, production of organic acids, antibiotic resistance, and survival under digestive stresses using an in vitro gut model. The strain L. plantarum Lp 187_B2 , which produced the highest riboflavin level (6 mg/L), exhibited good resistance to gastro-intestinal stress and a relevant capacity to antagonize undesired bacteria, was selected for additional investigations to assess its capacity to protect intestinal homeostasis. When used as a postbiotic, Lp 187_B2 significantly increased trans-epithelial electrical resistance (TEER) in Caco-2 cell monolayers, an in vitro model of the intestinal barrier. Moreover, in a Caco-2/THP-1 co-culture system, mimicking the inflamed bowel, Lp 187_B2 postbiotics significantly inhibited the release of TNF-α by macrophages, thus pointing to gut-barrier strengthening and potential anti-inflammatory properties. Though a validation in vivo is required, our preliminary results indicate that L. plantarum Lp 187_B2 could be successfully applied as both probiotic and postbiotic formulations for improving human health.

Managing tuberculosis infection among migrants from high-incidence tuberculosis countries: challenges, strategies and recommendations - Salvatore Rotundo; Francesca Serapide; Gabriella d’Ettorre; Maria Teresa Tassone; Mattia Albanese; Gabriella Giuseppina Marino; Bruno Tassone; Giancarlo Ceccarelli; Alessandro Russo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Tuberculosis (TB) remains a significant global health challenge, especially in countries with low TB incidence, exacerbated by the influx of migrants from high TB-burden regions. This paper reviews the challenges and strategies for managing TB infection (TBI) among migrants. Challenges in screening and treating TBI among migrants include diagnostic limitations of available tests which are tuberculin skin test (TST) and interferon-gamma release assay (IGRA), socioeconomic barriers, cultural beliefs and mobility. Recommendations vary among guidelines, ranging from proactive screening to targeted approaches. We addressed the issue of two-step testing, discussing the use of an initial TST followed by IGRA confirmation, with consideration of BCG vaccination status and TB exposure history. Treatment options for TBI include isoniazid monotherapy and rifamycin-based regimens in most cases, with varying preferences across guidelines. Challenges in TBI treatment include hepatotoxicity and adherence issues, particularly among migrants. Overall, a comprehensive approach addressing socioeconomic, cultural, and structural factors is crucial for effective TBI management among migrants. Collaboration between healthcare providers, policymakers and migrant communities is essential for developing culturally sensitive screening and treatment protocols. Further research is needed to evaluate the efficacy and feasibility of different screening and treatment strategies, particularly among migrant populations.

Formulated Diets Drive Gonadal Maturity but Reduce Larval Success in Paracentrotus lividus - Bruno Pinto; Maissa Gharbi; Serena Federico; Francesca Glaviano; Enea Tentoni; Tania Russo; Anna Di Cosmo; Gianluca Polese; Maria Costantini; Valerio Zupo (Journal of Marine Science and Engineering, 2025)
Over the past few decades, demand for sea urchin roe has risen, while wild sea urchin populations have declined. This trend has increased interest in aquaculture techniques and the development of formulated feeds to support ecological restoration and research. Here, we examined the effects of a high-protein formulated feed on gonad development in Paracentrotus lividus, compared to fresh feeds (maize and spinach), across three replicated tanks. We assessed gonad maturation, gamete viability, and larval development, and developed a new histopathological index applicable to both sexes. Formulated feed significantly enhanced gonad maturation, increased gamete production, and led to heavier gonads with higher gonadosomatic indices compared to fresh feeds, which were insufficient to promote maturation within four weeks. Notably, no histological alterations were observed in the gonads. Fertilization trials showed that embryos were produced, but none reached the pluteus stage, indicating decreased embryo viability. Although the formulated feed improved gonad development, it adversely affected water quality, increasing nutrient concentrations and lowering pH. Overall, these findings suggest that high-protein formulated feeds could potentially improve aquaculture production by enhancing gonad maturation and gamete output, but additional measures may be needed to support complete larval development.

Heatwaves Affect the Gonadal Maturation of the Sea Urchin Paracentrotus lividus - Amalia Amato; Tania Russo; Davide Caramiello; Alberto Macina; Anna Di Cosmo; Gianluca Polese; Valerio Zupo; Maria Costantini (Journal of Marine Science and Engineering, 2025)
Climate-induced ocean warming poses a major threat to marine invertebrate reproduction, including the sea urchin Paracentrotus lividus, a species of considerable ecological, economic, and scientific interest. Its gonads, highly valued as a culinary delicacy, support local fisheries and aquaculture industries, making reproductive health a critical factor for both conservation and commercial viability. The present study reported the effects of elevated seawater temperatures, mimicking marine heatwave (MHW) conditions, on gonadal maturation and fertilization success on P. lividus. Here, adult specimens at the mature stage of gametogenesis were exposed to control (18 °C) and elevated temperature regimes (24 °C) over a six-week period, and key reproductive metrics were assessed, including histological analysis. Morphological analysis showed very evident gonadal retraction, nearly devoid of germ cells, both for males and females, with a significant decrease in the gonadal index. In addition, histological analysis revealed consistent damage to the gonads, with a significantly increase in histopathological index in specimens kept at 24 °C. These findings reinforce the temperature sensitivity of P. lividus reproduction, suggesting that recurrent heatwaves could severely impair its reproductive output and population dynamics with potential cascading effects on benthic community structure in a long-term ocean warming predicted to intensify.

Data centric Artificial Intelligence for agrifood domain: A systematic mapping study - Domenico Benfenati; Domenico Amalfitano; Cristiano Russo; Cristian Tommasino; Antonio Maria Rinaldi (Computers and Electronics in Agriculture, 2025)

Gendered dimensions of mental health in High-Risk occupations: A systematic review of the mining and extractive sectors - Ana Carolina Russo; Rita Aparecida Longo Russo; Maria Renata Machado Stellin; Sérgio Médici de Eston (The Extractive Industries and Society, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Beyond the standard: a comprehensive review of innovative experimental models using Tenebrio molitor larvae - Anamaria Mendonça Santos; Cláudio Carvalho Santana Júnior; José Adão Carvalho Nascimento Júnior; Ana Maria Santos Oliveira; Gomathi Rajkumar; Izabel Almeida Alves; Mairim Russo Serafini (Biologia Futura, 2025)

The italian national genomic strategy: current status, challenges, and future perspectives in clinical practice and public health - Francesco Andrea Causio; Sara Farina; Alessandra Maio; Flavia Beccia; Luigi Russo; Valentina Baccolini; Matteo Chiara; Americo Cicchetti; Gualtiero I. Colombo; Giovanni Comandé; Domenico Coviello; Ruggero De Maria; et al. (Journal of Community Genetics, 2025)
This article presents the outcomes of a national initiative aimed at developing a technical document to support the future Italian National Genomic Strategy, carried out from 2021 to 2024 through the collaboration of 14 research institutions. The project was designed to align with major European genomic initiatives, particularly the “1 + Million Genomes” (1 + MG) Declaration and its supporting programs, including Beyond 1 Million Genomes (B1 + MG), the Genomic Data Infrastructure (GDI), and Genome of Europe (GoE). The initiative was structured around 12 National Mirror Groups (NMGs), each addressing a specific domain such as clinical implementation, ethical and legal issues, data governance, health economics, and public engagement. Through expert consensus and coordinated activities, the project produced a comprehensive technical document outlining seven strategic lines and related intervention areas. These include the integration of genomic testing into clinical practice, development of specialized genomic centers, creation of a national genomic data infrastructure, professional training, and public education. The proposed strategy emphasizes equitable access to genomic medicine, the use of health technology assessment to evaluate new technologies, and the importance of citizen engagement and literacy. By fostering collaboration among institutions, healthcare professionals, and the public, the final goal is to position Italy as a leader in genomic medicine and ensure the responsible, effective, and ethical use of genomics in public health and clinical care.

Response Surface Methodology as a tool to obtain a potential satiating bitter enriched extract from Gentiana lutea L. - Vittorio Carlucci; Maria Ponticelli; Ludovica Lela; Claudia Mangieri; Federica Santopietro; Immacolata Faraone; Daniela Russo; Luigi Milella (Phytochemistry Letters, 2025)

Secondary metabolites produced by Nigrospora sphaerica associated with the invasive weed Cenchrus ciliaris - Maria Michela Salvatore; Maria Teresa Russo; Susan Meyer; Angela Tuzi; Marina DellaGreca; Marco Masi; Anna Andolfi (Phytochemistry Letters, 2025)

Human exposure to PFASs in a contaminated area: associations between water and serum levels - Anna Maria Ingelido; Valentina Fuscoletti; Annalisa Abballe; Mario Cerroni; Elena Dellatte; Nicola Iacovella; Valentina Marra; Silvia Valentini; Luca Lucentini; Elena De Felip; Francesca Russo (Chemosphere, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Global trends in urban forest irrigation: Environmental influences, challenges and opportunities for sustainable practices across 109 cities worldwide - Manuel Esperon-Rodriguez; Rachael V Gallagher; Alessio Russo; Sally A Power; Pedro Calaza-Martínez; Tiago Capela Lourenço; Paloma Cariñanos; Ana Alice Eleuterio; Zhengfei Guo; Gervais Lee; Pierre Masselot; Robert I. Mcdonald; et al. (Sustainable Cities and Society, 2025)

Insulin resistance and cancer: molecular links and clinical perspectives - Alfredo Caturano; Enes Erul; Roberto Nilo; Davide Nilo; Vincenzo Russo; Luca Rinaldi; Carlo Acierno; Maria Gemelli; Riccardo Ricotta; Ferdinando Carlo Sasso; Antonio Giordano; Caterina Conte; et al. (Molecular and Cellular Biochemistry, 2025)

Risk factors for the development of hospital-acquired pneumonia in patients with carbapenem-resistant Acinetobacter baumannii respiratory colonization and the role of multisite colonization: a multicenter retrospective study - Alessandro Russo; Francesca Serapide; Francesco Alessandri; Sara Palma Gullì; Andrea Bruni; Federico Longhini; Angela Quirino; Rocco Morena; Nadia Marascio; Giovanni Matera; Gabriella d’Ettorre; Veronica Zullino; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Introduction Carbapenem-resistant Acinetobacter baumannii (CRAB) infections are associated with high morbidity and mortality rates. Furthermore, the role of CRAB respiratory colonization, including multisite colonization, has not yet been adequately highlighted in critically ill patients. Materials and methods In this retrospective multicenter study, conducted in 4 different Italian hospitals, patients with CRAB respiratory colonization +/- other site who developed or did not develop clinically significant pneumonia from December 2015 to December 2023 were enrolled. The primary objective of the study was to identify risk factors associated with the development of pneumonia. Results 760 patients were enrolled; among them, 392 (51.5%) developed pneumonia, while 304 (39.9%) patients presented multisite colonization. Overall, in-hospital mortality was 76.3% with a higher mortality (79.6%) in patients who developed pneumonia ( p = 0.033). In logistic regression analysis, factors associated with the development of pneumonia included: age, immunosuppressive therapy, COPD, ventilatory support and multisite colonization. A score was developed with AUC 0.72, CI95% 0.68–0.75, p < 0.001 and a sensitivity of 79% and specificity of 55% with a score > 2 and a maximum score of 10 points. Multisite colonization was recorded more frequently in patients who developed pneumonia (51%, p < 0.001). Finally, Kaplan-Meier curves showed a significantly reduced survival at 30 days ( p = 0.005) and throughout the hospital stay ( p = 0.002) in patients with multisite colonization. Conclusions This study highlights the risk factors associated with the development of pneumonia in patients already colonized by CRAB. Multisite colonization showed an important role as a risk factor for the development of pneumonia and for its correlation with mortality. Clinical trial number Not applicable.

Unveiling cardiovascular and respiratory toxicities with monoclonal antibodies in multiple myeloma: disproportionality analysis from the FDA Adverse Event Reporting System - Maria Antonietta Barbieri; Giulia Russo; Giuseppe Cicala; Giuseppe Andò; Tindara Franchina; Nicola Silvestris; Mariacarmela Santarpia; Edoardo Spina (European Journal of Clinical Pharmacology, 2025)

Highest oxygen consumption prediction: introducing variable theoretical proportional factors for different sports - Irma Lorenzo-Capellá; Juan José Ramos-Álvarez; Maria Elena Jiménez-Herranz; Nicola Maffulli; Edilson Fernando de Borba; Enzo Iuliano; Francisco Javier Calderón-Montero; Luca Paolo Ardigò; Luca Russo; Johnny Padulo (European Journal of Applied Physiology, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Genomic diversity in time and space in the toxic diatom Pseudo-nitzschia multistriata - Svenja Mager; Francesco Manfellotto; Antonella Ruggiero; Viviana Di Tuccio; Federica Cerino; Stefano Accoroni; Tomohiro Nishimura; Marta Mikhno; Neri Fattorini; Timotej Turk Dermastia; Jasna Arapov; Sanda Skejic; et al. (Harmful Algae, 2025)

Environmental, climatic, socio-economic factors and non-pharmacological interventions: A comprehensive four-domain risk assessment of COVID-19 hospitalization and death in Northern Italy - Lucia Palandri; Cristiana Rizzi; Vittoria Vandelli; Tommaso Filippini; Alessandro Ghinoi; Giuliano Carrozzi; Gianfranco De Girolamo; Isabella Morlini; Paola Coratza; Enrico Giovannetti; Margherita Russo; Mauro Soldati; et al. (International Journal of Hygiene and Environmental Health, 2025)

Re-evaluating beauty: Attitudes and perceptions of eco-friendly packaging in beauty care products - A systematic review - Alexia Del Greco; Marco Bani; Giulia Rampoldi; Stefano Ardenghi; Paolo Galli; Maria Grazia Strepparava; Selena Russo (Sustainable Production and Consumption, 2024)

Probiotic Lactiplantibacillus plantarum strains showing anti-Botrytis activity: A food-grade approach to improve the overall quality of strawberry in post-harvest - Nicola De Simone; Angela Scauro; Danial Fatchurrahman; Maria Luisa Amodio; Vittorio Capozzi; Giancarlo Colelli; Giuseppe Spano; Mariagiovanna Fragasso; Pasquale Russo (Postharvest Biology and Technology, 2024)

DLP 3D printing of alumina catalyst architectures: Design, kinetics and modeling of structure effects on catalyst performance - Luca Mastroianni; Ananias De Jesus Medina Ferrer; Anna Maria De Domenico; Kari Eränen; Martino Di Serio; Dmitry Murzin; Vincenzo Russo; Tapio Salmi (Chemical Engineering Journal, 2024)

Effects of Crotalaria spectabilis extract in Meloidogyne javanica and Heterodera glycines soybean nematodes - Tamires Scupinari; Helena Mannochio-Russo; Gustavo Galo Marcheafave; Vanderlan da Silva Bolzani; Estela de Oliveira Nunes; Waldir Pereira Dias; Clara Beatriz Hoffmann-Campo; Maria Luiza Zeraik (European Journal of Plant Pathology, 2024)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

The combined use of biological investigations, bio chromatographic and in silico methods to solve the puzzle of badge and its derivative's toxicity - Ilaria Neri; Marialuisa Piccolo; Giacomo Russo; Maria Grazia Ferraro; Vincenzo Marotta; Rita Santamaria; Lucia Grumetto (Chemosphere, 2024)

Unlocking glycerol Potential: Novel pathway for hydrogen production and Value-Added chemicals - Alessandra Di Nardo; Gianluca Landi; Giuseppina Luciani; Maria Portarapillo; Giovanna Ruoppolo; Danilo Russo; Armando Zarrelli; Almerinda Di Benedetto (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Anti-biofilm properties of Portuguese honeys against multi-drug resistant microorganisms: A promising strategy for chronic wounds healing - Andrea Bezerra; Maria José Alves; Maria José Saavedra; Paulo Russo-Almeida; Alfredo Aires; Hélder Fonseca; Francisca Rodrigues; Cristina Delerue-Matos; Juliana Garcia; Irene Gouvinhas (Food Bioscience, 2024)

The Tiny Big Difference: Nanotechnology in Photoprotective Innovations – A Systematic Review - José Adão Carvalho Nascimento Júnior; Anamaria Mendonça Santos; Ana Maria Santos Oliveira; Alcimary Bispo Santos; Adriano Antunes de Souza Araújo; Diana Marcela Aragón; Luiza Abrahão Frank; Mairim Russo Serafini (AAPS PharmSciTech, 2024)

Sustainable cultivation of Porphyridium cruentum via agro-industrial by-products: A study on biomass and lipid enhancement - Giovanni Luca Russo; Antonio Luca Langellotti; Vito Verardo; Beatriz Martin Garcia; Maria Oliviero; Paolo Masi (Biocatalysis and Agricultural Biotechnology, 2024)

Exploring the biofilm inhibitory potential of Candida sp. UFSJ7A glycolipid on siliconized latex catheters - Cibele Garcia Bastos; Diego Fernandes Livio; Maria Auxiliadora de Oliveira; Hiure Gomes Ramos Meira; Vinícius Souza Tarabal; Heloísa Carneiro Colares; Adriano Guimarães Parreira; Rafael César Russo Chagas; Marcelo Gomes Speziali; José Antônio da Silva; José Mauro Granjeiro; Ruben Dario Sinisterra Millán; et al. (Brazilian Journal of Microbiology, 2024)

First report of 6-methylpyridione analogues from Dothiorella sarmentorum, a botryosphaeriaceous fungus associated with grapevine trunk diseases - Maria Michela Salvatore; Rosario Nicoletti; Maria Teresa Russo; Alla Eddine Mahamedi; Akila Berraf-Tebbal; Marina DellaGreca; Andolfi Anna (Natural Product Research, 2024)

Production and characterization of the lipopeptide with anti-adhesion for oral biofilm on the surface of titanium for dental implants - Fernanda Souza Carvalho; Vinícius Souza Tarabal; Diego Fernandes Livio; Luísa F. Cruz; Ana P.F. Monteiro; Adriano Guimarães Parreira; Pedro P.G. Guimarães; Karina Scheuerman; Rafael Cesar Russo Chagas; José Antônio da Silva; Daniel Bonoto Gonçalves; José Mauro Granjeiro; et al. (Archives of Microbiology, 2024)

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Effect of biodegradable polymers upon grazing activity of the sea urchin Paracentrotus lividus (Lmk) revealed by morphological, histological and molecular analyses - Thomas Viel; Mariacristina Cocca; Roberta Esposito; Amalia Amato; Tania Russo; Anna Di Cosmo; Gianluca Polese; Loredana Manfra; Giovanni Libralato; Valerio Zupo; Maria Costantini (Science of The Total Environment, 2024)

Reproductive toxicity assessment of cellulose nanofibers, citric acid, and branched polyethylenimine in sea urchins: Eco-design of nanostructured cellulose sponge framework (Part B) - Maria Consiglia Esposito; Laura Riva; Gian Luigi Russo; Carlo Punta; Ilaria Corsi; Elisabetta Tosti; Alessandra Gallo (Environmental Pollution, 2024)

Immunomodulatory Activity on Human Macrophages by Cell-Free Supernatants to Explore the Probiotic and Postbiotic Potential of Lactiplantibacillus plantarum Strains of Plant Origin - Maria Teresa Rocchetti; Pasquale Russo; Nicola De Simone; Vittorio Capozzi; Giuseppe Spano; Daniela Fiocco (Probiotics and Antimicrobial Proteins, 2024)
Upon dietary administration, probiotic microorganisms can reach as live cells the human gut, where they interact with the microbiota and host cells, thereby exerting a beneficial impact on host functions, mainly through immune-modulatory activities. Recently, attention has been drawn by postbiotics, i.e. non-viable probiotic microbes, including their metabolic products, which possess biological activities that benefit the host. Lactiplantibacillus plantarum is a bacterial species that comprises recognised probiotic strains. In this study, we investigated in vitro the probiotic (and postbiotic) potential of seven L. plantarum strains, including five newly isolated from plant-related niches. The strains were shown to possess some basic probiotic attributes, including tolerance to the gastrointestinal environment, adhesion to the intestinal epithelium and safety. Besides, their cell-free culture supernatants modulated cytokine patterns in human macrophages in vitro, promoting TNF-α gene transcription and secretion, while attenuating the transcriptional activation and secretion of both TNF-α and IL-8 in response to a pro-inflammatory signal, and enhancing the production of IL-10. Some strains induced a high IL-10/IL-12 ratio that may correlate to an anti-inflammatory capacity in vivo. Overall, the investigated strains are good probiotic candidates, whose postbiotic fraction exhibits immunomodulatory properties that need further in vivo studies. The main novelty of this work consists in the polyphasic characterisation of candidate beneficial L. plantarum strains obtained from relatively atypical plant-associated niches, by an approach that explores both probiotic and postbiotic potentials, in particular studying the effect of microbial culture-conditioned media on cytokine pattern, analysed at both transcriptional and secretion level in human macrophages.

Morphometry of Lamiaceae pollen grains from the archaeological site of Kastrì (Epirus-Greece; 15th–16th cent. AD) - Chiara Comegna; Elda Russo Ermolli; Valentino Di Donato; Anthi Angeli; Brunella Gargiulo; Dimitris Roubis; Francesca Sogliani; Maria Rosaria Barone Lumaga (Review of Palaeobotany and Palynology, 2024)

Molecular monitoring of viral infections in immunocompromised patients in a large university hospital in Italy: reflections after thirteen years of real-life activity - Lilia Cinti; Piergiorgio Roberto; Matteo Rossi; Anna Napoli; Gianluca Russo; Anna Paola Iori; Giuseppe Gentile; Maria Augurusa; Corrado Girmenia; Guido Antonelli; Aurelia Gaeta (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose This study aimed to investigate the prevalence and viral reactivations of clinical interest in the immunocompromised patient with particular focus on hematologic and solid organ transplant recipients. Methods Molecular screening data of CMV, EBV, JCV and BKV from 2011 to 2023 were analyzed. This extensive time span allowed the access to more than 100,000 samples from over 20,000 patients treated at Policlinico Umberto I. It was possible to temporally investigate patient attendance patterns, average age distribution, seasonality of infections, and positivity rates of the analyzed viruses. Results Between 2019 and 2022 a significant reduction in organ transplants performed and in the positive molecular detection of EBV, JCV and BKV was observed. Additionally, there has been a noteworthy decrease in CMV reactivations, with a reduction of up to 50% starting in 2019. A remarkable reduction of 39% in the rate of CMV viral reactivation has been also achieved in SOT between 2016 and 2023. Conclusion The years following 2019 were profoundly impacted by the COVID-19 pandemic era. This period resulted in a substantial reduction in healthcare services and hospital visits. Furthermore, the introduction of the drug Letermovir in Italy in 2019 demonstrated remarkable efficacy, evidenced by a reduction in CMV reactivations. Additionally, the adoption of a novel clinical approach centered on personalized therapy facilitated improved management of immunocompromised patients.

Environmental DNA metabarcoding reveals the effects of seafloor litter and trawling on marine biodiversity - Alice Sbrana; Giulia Maiello; Maria Flavia Gravina; Davide Cicala; Simone Galli; Matteo Stefani; Tommaso Russo (Marine Environmental Research, 2024)

Fluoride adsorption on hydroxyapatite: From batch to continuous operation - Vincenzo Russo; Antonio D’Angelo; Clorinda Salvi; Rosanna Paparo; Michele Emanuele Fortunato; Elisabetta Maria Cepollaro; Oreste Tarallo; Marco Trifuoggi; Martino Di Serio; Riccardo Tesser (Journal of Environmental Chemical Engineering, 2024)

Trophic niche overlap of deep-sea fish species revealed by the combined approach of stomach contents and stable isotopes analysis in the Central Tyrrhenian Sea - Davide Cicala; Alice Sbrana; Tommaso Valente; Daniela Berto; Federico Rampazzo; Maria Flavia Gravina; Giulia Maiello; Tommaso Russo (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Identifying priority areas for spatial management of mixed fisheries using ensemble of multi‐species distribution models - Diego Panzeri; Tommaso Russo; Enrico Arneri; Roberto Carlucci; Gianpiero Cossarini; Igor Isajlović; Svjetlana Krstulović Šifner; Chiara Manfredi; Francesco Masnadi; Marco Reale; Giuseppe Scarcella; Cosimo Solidoro; et al. (Fish and Fisheries, 2024)
Spatial fisheries management is widely used to reduce overfishing, rebuild stocks, and protect biodiversity. However, the effectiveness and optimization of spatial measures depend on accurately identifying ecologically meaningful areas, which can be difficult in mixed fisheries. To apply a method generally to a range of target species, we developed an ensemble of species distribution models (e‐SDM) that combines general additive models, generalized linear mixed models, random forest, and gradient‐boosting machine methods in a training and testing protocol. The e‐SDM was used to integrate density indices from two scientific bottom trawl surveys with the geopositional data, relevant oceanographic variables from the three‐dimensional physical‐biogeochemical operational model, and fishing effort from the vessel monitoring system. The determined best distributions for juveniles and adults are used to determine hot spots of aggregation based on single or multiple target species. We applied e‐SDM to juvenile and adult stages of 10 marine demersal species representing 60% of the total demersal landings in the central areas of the Mediterranean Sea. Using the e‐SDM results, hot spots of aggregation and grounds potentially more selective were identified for each species and for the target species group of otter trawl and beam trawl fisheries. The results confirm the ecological appropriateness of existing fishery restriction areas and support the identification of locations for new spatial management measures.

What, where, and when: Spatial-temporal distribution of macro-litter on the seafloor of the western and central Mediterranean sea - Alessandro Cau; Alice Sbrana; Simone Franceschini; Fabio Fiorentino; Maria Cristina Follesa; Francois Galgani; Germana Garofalo; Olivia Gerigny; Adriana Profeta; Paola Rinelli; Mario Sbrana; Tommaso Russo (Environmental Pollution, 2024)

Assessing the role of atmospheric dispersion vs. emission strength in the southern Po Valley (Italy) using dispersion-normalised multi-time receptor modelling - Federica Crova; Alice Corina Forello; Vera Bernardoni; Giulia Calzolai; Silvia Canepari; Stefania Argentini; Francesca Costabile; Maria Agostina Frezzini; Fabio Giardi; Franco Lucarelli; Dario Massabò; Lorenzo Massimi; et al. (Atmospheric Environment, 2024)

Effect of microbial fermentation on functional traits and volatiloma profile of pâté olive cake - Paola Foti; Cinzia L. Randazzo; Mariateresa Russo; Rosa Di Sanzo; Flora V. Romeo; Antonio Scilimati; Morena Miciaccia; Maria Grazia Perrone; Cinzia Caggia (Food Research International, 2023)

Geochemical Behaviour of Rare Earth Elements Throughout an Acid Mine Drainage Passive Treatment System in the Lousal Mine Area, Portugal - Cynthia Obregón-Castro; Maria Isabel Prudêncio; Catarina Diamantino; Edgar Carvalho; Dulce Russo; Rosa Marques (Mine Water and the Environment, 2023)
A passive remediation system was installed between 2010 and 2015 at the Lousal legacy mine site in southwestern Portugal to minimize the impact of AMD. This is the first study of the geochemical behaviour of rare earth elements (REE) in the area after implementation of the passive treatment system. The total and dissolved concentrations of REE is similar throughout the basins/wetlands and acidic ponds in both sampling campaigns, which is mainly attributed to the conservative behaviour of these elements in acidic water. In areas where mixing of acidic and circumneutral water occurs, the REE were partially removed from solution by adsorption onto newly formed Al and Fe precipitates. Sorption onto the precipitates varies between the rare earths, with a preferential fixation of heavy REE (HREE) compared to the light REE (LREE). The normalized distribution patterns exhibit the characteristic convex-up enrichment in middle rare earth elements for AMD and display an enrichment of LREE relative to HREE in areas where mixing of waters occurs, and the pH is close to circumneutral.

Nanostructured cellulose sponge engineered for marine environmental remediation: Eco-safety assessment of its leachate on sea urchin reproduction (Part A) - Maria Consiglia Esposito; Gian Luigi Russo; Laura Riva; Carlo Punta; Ilaria Corsi; Elisabetta Tosti; Alessandra Gallo (Environmental Pollution, 2023)

Antimicrobial Properties, Functional Characterisation and Application of Fructobacillus fructosus and Lactiplantibacillus plantarum Isolated from Artisanal Honey - Nicola De Simone; Maria Teresa Rocchetti; Barbara la Gatta; Giuseppe Spano; Djamel Drider; Vittorio Capozzi; Pasquale Russo; Daniela Fiocco (Probiotics and Antimicrobial Proteins, 2023)
Honey is a valuable reservoir of lactic acid bacteria (LAB) and, particularly, of fructophilic LAB (FLAB), a relatively novel subgroup of LAB whose functional potential for human and food application has yet to be explored. In this study, FLAB and LAB strains have been isolated from honeys of different floral origins and selected for their broad antimicrobial activity against typical foodborne pathogenic bacteria and spoilage filamentous fungi. The best candidates, two strains belonging to the species Lactiplantibacillus plantarum and Fructobacillus fructosus , were submitted to partial characterisation of their cell free supernatants (CFS) in order to identify the secreted metabolites with antimicrobial activity. Besides, these strains were examined to assess some major functional features, including in vitro tolerance to the oro-gastrointestinal conditions, potential cytotoxicity against HT-29 cells, adhesion to human enterocyte-like cells and capability to stimulate macrophages. Moreover, when the tested strains were applied on table grapes artificially contaminated with pathogenic bacteria or filamentous fungi, they showed a good ability to antagonise the growth of undesired microbes, as well as to survive on the fruit surface at a concentration that is recommended to develop a probiotic effect. In conclusion, both LAB and FLAB honey-isolated strains characterised in this work exhibit functional properties that validate their potential use as biocontrol agents and for the design of novel functional foods. We reported antimicrobial activity, cytotoxic evaluation, probiotic properties and direct food application of a F. fructosus strain, improving the knowledge of this species, in particular, and on FLAB, more generally.

Antimicrobial and antioxidant properties and quantitative screening of phytochemicals of Fraxinus excelsior L. and Eschscholtzia californica Cham. mother tinctures - Maria Grazia Bonomo; Daniela Russo; Immacolata Faraone; Luigi Milella; Stefania Mirela Mang; Carmela Saturnino; Maria Stefania Sinicropi; Alessia Catalano; Giovanni Salzano (Natural Product Research, 2023)

Place-based solutions for global social-ecological dilemmas: An analysis of locally grounded, diversified, and cross-scalar initiatives in the Amazon - Marina Londres; Carl Salk; Krister P. Andersson; Maria Tengö; Eduardo S. Brondizio; Gabriela Russo Lopes; Sacha M.O. Siani; Adriana Molina-Garzón; Taís Sonetti-González; Diego Rázuri Montoya; Célia Futemma; Fábio de Castro; et al. (Global Environmental Change, 2023)

Corrigendum to “Impacts of exhaust gas cleaning systems (EGCS) discharge waters on planktonic biological indicators” - Marco Picone; Martina Russo; Gabriele Giuseppe Distefano; Marco Baccichet; Davide Marchetto; Annamaria Volpi Ghirardini; Anna Lunde Hermansson; Mira Petrovic; Meritxell Gros; Elisa Garcia; Elisa Giubilato; Loris Calgaro; et al. (Marine Pollution Bulletin, 2023)

Remdesivir treatment and clinical outcome in non-severe hospitalized COVID-19 patients: a propensity score matching multicenter Italian hospital experience - Emilio Attena; Alfredo Caturano; Anna Annunziata; Alberto Enrico Maraolo; Annunziata De Rosa; Francesco Maria Fusco; Geza Halasz; Valeria Dall’Ospedale; Maddalena Conte; Valentina Parisi; Raffaele Galiero; Ferdinando Carlo Sasso; et al. (European Journal of Clinical Pharmacology, 2023)
Introduction Remdesivir exerts positive effects on clinical improvement, even though it seems not to affect mortality among COVID-19 patients; moreover, it was associated with the occurence of marked bradycardia. Methods We retrospectively evaluated 989 consecutive patients with non-severe COVID-19 (SpO 2 ≥ 94% on room air) admitted from October 2020 to July 2021 at five Italian hospitals. Propensity score matching allowed to obtain a comparable control group. Primary endpoints were bradycardia onset (heart rate < 50 bpm), acute respiratory distress syndrome (ARDS) in need of intubation and mortality. Results A total of 200 patients (20.2%) received remdesivir, while 789 standard of care (79.8%). In the matched cohorts, severe ARDS in need of intubation was experienced by 70 patients (17.5%), significantly higher in the control group (68% vs. 31%; p < 0.0001). Conversely, bradycardia, experienced by 53 patients (12%), was significantly higher in the remdesivir subgroup (20% vs. 1.1%; p < 0.0001). During follow-up, all-cause mortality was 15% ( N = 62), significantly higher in the control group (76% vs. 24%; log-rank p < 0.0001), as shown at the Kaplan–Meier (KM) analysis. KM furthermore showed a significantly higher risk of severe ARDS in need of intubation among controls (log-rank p < 0.001), while an increased risk of bradycardia onset in the remdesivir group (log-rank p < 0.001). Multivariable logistic regression showed a protective role of remdesivir for both ARDS in need of intubation (OR 0.50, 95%CI 0.29–0.85; p = 0.01) and mortality (OR 0.18, 95%CI 0.09–0.39; p < 0.0001). Conclusions Remdesivir treatment emerged as associated with reduced risk of severe acute respiratory distress syndrome in need of intubation and mortality. Remdesivir-induced bradycardia was not associated with worse outcome.

A new ginger extract characterization: Immunomodulatory, antioxidant effects and differential gene expression - Roberta Russo; Maria Assunta Costa; Nadia Lampiasi; Marco Chiaramonte; Alessia Provenzano; Maria Rosalia Mangione; Rosa Passantino; Francesca Zito (Food Bioscience, 2023)

Specialized metabolites from plants as a source of new multi-target antiviral drugs: a systematic review - Maria Ponticelli; Maria Laura Bellone; Valentina Parisi; Annamaria Iannuzzi; Alessandra Braca; Nunziatina de Tommasi; Daniela Russo; Annalisa Sileo; Paola Quaranta; Giulia Freer; Mauro Pistello; Luigi Milella (Phytochemistry Reviews, 2023)
Viral infections have always been the main global health challenge, as several potentially lethal viruses, including the hepatitis virus, herpes virus, and influenza virus, have affected human health for decades. Unfortunately, most licensed antiviral drugs are characterized by many adverse reactions and, in the long-term therapy, also develop viral resistance; for these reasons, researchers have focused their attention on investigating potential antiviral molecules from plants. Natural resources indeed offer a variety of specialized therapeutic metabolites that have been demonstrated to inhibit viral entry into the host cells and replication through the regulation of viral absorption, cell receptor binding, and competition for the activation of intracellular signaling pathways. Many active phytochemicals, including flavonoids, lignans, terpenoids, coumarins, saponins, alkaloids, etc., have been identified as potential candidates for preventing and treating viral infections. Using a systematic approach, this review summarises the knowledge obtained to date on the in vivo antiviral activity of specialized metabolites extracted from plant matrices by focusing on their mechanism of action.

Comparative phylogeography reveals the demographic patterns of neotropical ancient mountain species - Marcos Vinicius Dantas‐Queiroz; Fernanda Hurbath; Fernanda Maria de Russo Godoy; Flávia Mol Lanna; Leonardo M. Versieux; Clarisse Palma‐Silva (Molecular Ecology, 2023)
Mountains are renowned for their bountiful biodiversity. Explanations on the origin of such abundant life are usually regarded to their orogenic history. However, ancient mountain systems with geological stability also exhibit astounding levels of number of species and endemism, as illustrated by the Brazilian Quartzitic Mountains (BQM) in Eastern South America. Thus, cycles of climatic changes over the last couple million years are usually assumed to play an important role in the origin of mountainous biota. These climatic oscillations potentially isolated and reconnected adjacent populations, a phenomenon known as flickering connectivity, accelerating speciation events due to range fragmentation, dispersion, secondary contact, and hybridization. To evaluate the role of the climatic fluctuations on the diversification of the BQM biota, we estimated the ancient demography of distinct endemic species of animals and plants using hierarchical approximate Bayesian computation analysis and Ecological Niche Modelling. Additionally, we evaluated if climatic oscillations have driven a genetic spatial congruence in the genetic structure of codistributed species from the Espinhaço Range, one of the main BQM areas. Our results show that the majority of plant lineages underwent a synchronous expansion over the Last Glacial Maximum (LGM, c. 21 thousand years ago), although we could not obtain a clear demographic pattern for the animal lineages. We also obtained a signal of a congruent phylogeographic break between lineages endemic to the Espinhaço Range, suggesting how ancient climatic oscillations might have driven the evolutionary history of the Espinhaço 's biota.

Impacts of exhaust gas cleaning systems (EGCS) discharge waters on planktonic biological indicators - Marco Picone; Martina Russo; Gabriele Giuseppe Distefano; Marco Baccichet; Davide Marchetto; Annamaria Volpi Ghirardini; Anna Lunde Hermansson; Mira Petrovic; Meritxell Gros; Elisa Garcia; Elisa Giubilato; Loris Calgaro; et al. (Marine Pollution Bulletin, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Lipophilicity profiling and cell viability assessment of a selected panel of endocrine disruptors - Giacomo Russo; Marialuisa Piccolo; Ilaria Neri; Maria Grazia Ferraro; Rita Santamaria; Lucia Grumetto (Chemosphere, 2023)

Determination of particulate polycyclic aromatic hydrocarbons in ambient air by gas chromatography-mass spectrometry after molecularly imprinted polymer extraction - Maria Chiara Pietrogrande; Giorgia Demaria; Mara Russo (Journal of Environmental Sciences, 2023)

Genetic diversity and population structure of Aechmea distichantha (Bromeliaceae), a widely geographically distributed species in South America - Fernanda Maria de Russo Godoy; Luciana Vicente-Silva; Marcos Vinícius Dantas-Queiroz; Clarisse Palma-Silva; Gecele Matos Paggi (Plant Systematics and Evolution, 2023)

Mate Perception and Gene Networks Regulating the Early Phase of Sex in Pseudo-nitzschia multistriata - Pina Marotta; Camilla Borgonuovo; Anna Santin; Monia Teresa Russo; Francesco Manfellotto; Marina Montresor; Pasquale De Luca; Maria Immacolata Ferrante (Journal of Marine Science and Engineering, 2022)
Diatoms are photosynthetic microorganisms playing a key role in the functioning of aquatic ecosystems; they are at the base of the food web and are the main drivers of biogeochemical processes. These microalgae have a unique diplontic life cycle in which the vegetative phase entails a cell size reduction that would lead to the extinction of the cell population if the size was not restored, usually by sexual reproduction. The switch from asexual to sexual reproduction needs to be finely synchronized and regulated to ensure its success; to this aim, cells evolved complex chemical crosstalk that mediates mating. We focused our attention on the marine diatom Pseudo-nitzschia multistriata, investigating the reciprocal perception of the opposite mating type (MT) and the genes and signaling molecules putatively involved in the process. From previously available transcriptomic data, we selected a panel of genes deregulated during the early phase of sexual reproduction, confirming for some of them a role during mate perception and establishing a hierarchy governing their behavior. Moreover, we explored the nature of the molecules controlling sexual reproduction in this species, unveiling that the signaling is mediated by the secretion of protein and non-protein cues from the MT− and MT+, respectively. Our results point to a model in which the two MTs stimulate each other, but the stimulation by the MT− is amplified after MT+ perception in a positive feedback manner.

Why not? Motivations for entering a volunteer register for clinical trials during the COVID-19 pandemic - Selena Russo; Marco Bani; Marco Terraneo; Valeria Quaglia; Giampaolo Nuvolati; Rebecca Cavaliere; Serena Capici; Marina Elena Cazzaniga; Maria Grazia Strepparava (European Journal of Clinical Pharmacology, 2022)
Backgrounds Healthy volunteers play a key role in clinical trials and it is crucial to develop recruitment strategies that capitalise on their motivations and maximise their participation. The COVID-19 pandemic has shown the importance of finding motivated healthy volunteers for the development of new vaccines. Public registers represent a promising way to promote the participation of healthy volunteers in the research field, but their adoption is still limited. The current study aimed to explore the motivations of healthy volunteers to enrol in an Italian public register for clinical trials during the COVID-19 pandemic and their attitude toward participating in a phase 1 COVID-19 vaccine clinical trial. The impacts of different enrolling interview modalities (in person, by phone, by mail) on motivation, understanding of information and trust in researchers were also investigated. Methods An online survey investigating experience with COVID-19, motivations to enrol, trust in researchers, political and healthcare authorities and pharmacological companies was presented to people applying as healthy volunteers in the public register for clinical trials at Phase 1 Unit Research Centre of ASST Monza, Italy, and considering to participate in a COVID-19 vaccine clinical trial. Data were collected in June 2021. Results Altruistic motivations were the main driver for enrolling in the public register, while self-interested motivations were secondary. No gender differences were found. As for enrolling modalities, no differences emerged between in-person and interviews for motivation to enrol, understanding of information and trust in researchers. Email modality led to significantly lower volunteers’ satisfaction and understanding of information but similar trust in research. Conclusions This study supports the validity of different interview modalities (in person and by phone) for the enrolment of healthy volunteers for clinical trials and highlights the positive role of public registers for the recruitment procedures.

The rise and fall of an alien: why the successful colonizer Littorina saxatilis failed to invade the Mediterranean Sea - Luciano Bosso; Sonia Smeraldo; Danilo Russo; Maria Luisa Chiusano; Giorgio Bertorelle; Kerstin Johannesson; Roger K. Butlin; Roberto Danovaro; Francesca Raffini (Biological Invasions, 2022)

In vitro antiglycation and antioxidant properties of Eugenia pyriformis leaves and fruits - Giselle Lopes da Silva; Mariana Bordin Campideli; Anna Beatriz Sabino Ferrari; Helena Mannochio-Russo; Karina Fraige; Alessandra Cristina Dametto; Vanderlan da Silva Bolzani; Maria Luiza Zeraik (Natural Product Research, 2022)

Polycyclic aromatic hydrocarbons and their oxygenated derivatives in urban aerosol: levels, chemical profiles, and contribution to PM2.5 oxidative potential - Maria Chiara Pietrogrande; Dimitri Bacco; Giorgia Demaria; Mara Russo; Fabiana Scotto; Arianna Trentini (Environmental Science and Pollution Research, 2022)
The concentrations of polycyclic aromatic hydrocarbons (PAHs) and quinones, a subgroup of oxygenated PAHs (oxy-PAHs), were measured in PM 2.5 samples collected during warm (May–June 2019) and cold (February–March 2020) seasons in the city of Bologna, Italy. Total PAHs concentration was nearly double in winter (6.58 ± 1.03 ng m −3 ) compared with spring (3.16 ± 0.53 ng m −3 ), following the trend of the PM 2.5 mass concentration. Molecular diagnostic ratios suggested that, together with traffic, biomass burning was the dominant emission source contributing to the peaks of concentration of PM 2.5 registered in the cold season. Quinone level was constant in both seasons, being 1.44 ± 0.24 ng m −3 , that may be related to the increased secondary formation during warm season, as confirmed by the higher Σoxy-PAHs/ΣPAHs ratio in spring than in winter. The oxidative potential (OP) of the PM 2.5 samples was assessed using acellular dithiothreitol (DTT) and ascorbic acid (AA) assays. The obtained responses showed a strong seasonality, with higher volume-normalized (OP V ) values in winter than in spring, i.e., OP V DTT : 0.32 ± 0.15 nmol min −1 m −3 vs. 0.08 ± 0.03 nmol min −1 m −3 and OP V AA : 0.72 ± 0.36 nmol min −1 m −3 vs. 0.28 ± 0.21 nmol min −1 m −3 . Both OP V DTT and OP V AA responses were significantly associated with total PAHs, as a general descriptor of redox-active PAH derivatives, associated with co-emission from burning sources or secondary atmospheric oxidation of parent PAHs. Otherwise, only winter OP V DTT responses showed a significant correlation with total Ʃoxy-PAHs concentration.

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

A molecular framework for the systematics of the Mediterranean spindle-shells (Gastropoda, Neogastropoda, Fasciolariidae, Fusininae) - Giula Fassio; Paolo Russo; Giuseppe Bonomolo; Alexander E. Fedosov; Maria Vittoria Modica; Elisa Nocella; MARCO OLIVERIO (Mediterranean Marine Science, 2022)
A remarkably high diversity of native small spindle-shells (Gastropoda, Fasciolariidae, Fusininae) has been recently inventoried in the Mediterranean Sea, with 23 species identified based on shell morphology. They have almost invariably been classified in the genus Fusinus, and a few of them recently moved to other genera (Aptyxis Troschel 1868, Aegeofusinus Russo, 2017 and Gracilipurpura Jousseaume, 1880), mostly based on the sole shell features. We have reconstructed a molecular phylogenetic framework for the Mediterranean Fusininae, focusing on native species representative of the genus-level taxa. Our results confirmed that Fusinus s.s. (type species Murex colus Linnaeus, 1758) should be restricted to a group of large-shelled species from the Indo-West Pacific and does not fit any of the small-shelled Mediterranean fusinines. We confirm that Murex syracusanus Linnaeus, 1758 represents a distinct lineage, and show that for all the remaining species the pattern is suggestive of a single monophyletic radiation of small Mediterranean fusinines, for which the name Pseudofusus Monterosato, 1884 must be used.

Microalgae-Based PUFAs for Food and Feed: Current Applications, Future Possibilities, and Constraints - Anna Santin; Sergio Balzano; Monia Teresa Russo; Fortunato Palma Esposito; Maria Immacolata Ferrante; Martina Blasio; Elena Cavalletti; Angela Sardo (Journal of Marine Science and Engineering, 2022)
Microalgae are currently considered an attractive source of highly valuable compounds for human and animal consumption, including polyunsaturated fatty acids (PUFAs). Several microalgae-derived compounds, such as ω-3 fatty acids, pigments, and whole dried biomasses are available on the market and are mainly produced by culturing microalgae in open ponds, which can be achieved with low setup and maintenance costs with respect to enclosed systems. However, open tanks are more susceptible to bacterial and other environmental contamination, do not guarantee a high reproducibility of algal biochemical profiles and productivities, and constrain massive cultivation to a limited number of species. Genetic engineering techniques have substantially improved over the last decade, and several model microalgae have been successfully modified to promote the accumulation of specific value-added compounds. However, transgenic strains should be cultured in closed photobioreactors (PBRs) to minimize risks of contamination of aquatic environments with allochthonous species; in addition, faster growth rates and higher yields of compounds of interest can be achieved in PBRs compared to open ponds. In this review, we present information collected about the major microalgae-derived commodities (with a special focus on PUFAs) produced at industrial scale, as well genetically-engineered microalgae to increase PUFA production. We also critically analyzed the main bottlenecks that make large-scale production of algal commodities difficult, as well as possible solutions to overcome the main problems and render the processes economically and environmentally safe.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

N-acetylcysteine aggravates seizures while improving depressive-like and cognitive impairment comorbidities in the WAG/Rij rat model of absence epilepsy - Martina Tallarico; Antonio Leo; Lorenza Guarnieri; Maria Caterina Zito; Carmen De Caro; Ferdinando Nicoletti; Emilio Russo; Andrew Constanti; Giovambattista De Sarro; Rita Citraro (Molecular Neurobiology, 2022)

Practical Marine Spatial Management of Ecologically or Biologically Significant Marine Areas: Emerging Lessons From Evidence-Based Planning and Implementation in a Developing-World Context - Linda R. Harris; Stephen D. Holness; Gunnar Finke; Maria Amunyela; Rodney Braby; Nelson Coelho; Kira Gee; Stephen P. Kirkman; Anja Kreiner; Elisabeth Mausolf; Prideel Majiedt; Erich Maletzky; et al. (Frontiers in Marine Science, 2022)
Identifying key sites of marine biodiversity value and implementing the required practical spatial management measures is critical for safeguarding marine biodiversity and maintaining essential ecological processes, especially in the face of accelerating global change and expanding ocean economies. Delineating Ecologically or Biologically Significant Marine Areas (EBSAs) has been catalytic in progressing toward this aim. However, the Benguela Current Large Marine Ecosystem (BCLME; comprising three developing countries: Angola, Namibia, and South Africa) is one of few places where practical action to secure biodiversity in EBSAs has followed their description. We aim to document the process of moving from biodiversity priority areas to implemented conservation actions, and distil broadly applicable emerging lessons. EBSAs in the BCLME were reviewed using a systematic conservation planning approach, supplemented with expert input. In this data- and knowledge-driven process, the boundaries and descriptions of existing EBSAs were refined, and gaps filled with new EBSAs. The status of 29 EBSAs was assessed by determining the ecological condition, ecosystem threat status, and ecosystem protection level of constituent ecosystem types. Also, current human uses and their respective impacts were systematically reviewed per EBSA. Management recommendations were proposed by dividing EBSAs into zones with associated multi-sector sea-use guidelines. Throughout the process, facilitated by a regional cooperation project, there was stakeholder engagement, and national, regional, and international review. BCLME States are currently implementing enhanced EBSA management in their respective marine spatial planning and marine protected area processes, noting that there are different but valid outcomes for securing marine biodiversity in each country. Further, the regional approach allowed for cross-border alignment of priorities and management between countries, as well as pooled expertise, technical support, and capacity development. Although full implementation is still underway, the lessons to date highlight some key factors required for a successful process that could guide similar initiatives elsewhere.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anti-inflammatory effect of a flavonoid-rich extract of orange juice in adult zebrafish subjected to Vibrio anguillarum -induced enteritis - Santa Cirmi; Basilio Randazzo; Caterina Russo; Laura Musumeci; Alessandro Maugeri; Giuseppe Montalbano; Maria Cristina Guerrera; Giovanni Enrico Lombardo; Maria Levanti (Natural Product Research, 2021)

Quantitative Real-Time PCR and Digital PCR to Evaluate Residual Quantity of HAV in Experimentally Depurated Mussels - Maria Grazia Amoroso; Denise Di Concilio; Antonio Luca Langellotti; Anna Martello; Barbara Cioffi; Elisabetta Suffredini; Loredana Cozzi; Valeria Russo; Gianluigi Mauriello; Simona Di Pasquale; Giorgio Galiero; Giovanna Fusco (Food and Environmental Virology, 2021)

Potential of Bacterial Strains Isolated from Ironstone Outcrops Bromeliads to Promote Plant Growth Under Drought Conditions - Rodrigo Mattos Silva Galeano; Fernanda Maria de Russo Godoy; Laís Mayara Melo Duré; Paulo Ivan Fernandes-Júnior; José Ivo Baldani; Gecele Matos Paggi; Fabiana Fonseca Zanoelo; Marivaine Silva Brasil (Current Microbiology, 2021)

Correction to: Coating Lacticaseibacillus rhamnosus GG in Alginate Systems: an Emerging Strategy Towards Improved Viability in Orange Juice - Angela Bonaccorso; Nunziatina Russo; Alessia Romeo; Claudia Carbone; Maria Aurora Grimaudo; Carmen Alvarez-Lorenzo; Cinzia Randazzo; Teresa Musumeci; Cinzia Caggia (AAPS PharmSciTech, 2021)

Eating Near the Dump: Identification of Nearby Plastic Hotspot as a Proxy for Potential Microplastic Contamination in the Norwegian Lobster (Nephrops norvegicus) - Simone Franceschini; Alessandro Cau; Lorenzo D’Andrea; Maria Cristina Follesa; Tommaso Russo (Frontiers in Marine Science, 2021)
Plastic waste dumped in the marine environment has severe ecological, social and economic impacts. In recent years, a series of scientific studies documented the contamination by macroplastic and its impact on marine organisms through the accidental ingestion of microplastics, which also originate from the degradation of macroplastic. However, the relationship between the spatial distribution of marine litter and the ingestion of plastics by organisms have never been related. In this work, we aimed to investigate, through a modeling approach, the relations between potential sources of microplastic particles (i.e., seafloor macroplastic accumulation hotspots detected by means of trawl surveys), and the ingestion by the benthic crustacean Norwegian lobster ( Nephrops norvegicus ). According to the literature, N. norvegicus is characterized by a sedentary behavior and therefore it has been highlighted as a proficient sentinel species for local microplastic contamination. Despite no significant relation has been found between microplastic ingestion and the local presence of seafloor macroplastic, it seems that proximity to hotspots of macroplastic accumulation is significantly related to microplastics ingestion. These results highlight important considerations on the fate of plastic in the marine environments with significant impacts on biota and the quality of the product caught at sea.

Effect of entomopathogenic fungi introduced as corn endophytes on the development, reproduction, and food preference of the invasive fall armyworm Spodoptera frugiperda - Maria L. Russo; Lara R. Jaber; Ana C. Scorsetti; Florencia Vianna; Marta N. Cabello; Sebastian A. Pelizza (Journal of Pest Science, 2021)

Effect of filter extraction solvents on the measurement of the oxidative potential of airborne PM2.5 - Maria Chiara Pietrogrande; Dimitri Bacco; Arianna Trentini; Mara Russo (Environmental Science and Pollution Research, 2021)
Solvent extraction of PM 2.5 samples collected on the filter is a preliminary step for assessing the PM 2.5 oxidative potential (OP) using cell-free assays, as the dithiothreitol (DTT) and the ascorbic acid (AA) assays. In this study, we evaluated the effect of the solvent choice by extracting ambient PM 2.5 samples with different solvents: methanol, as organic solvent, and two aqueous buffers, i.e., phosphate buffer (PB) and Gamble’s solution (G), as a lung fluid surrogate solution. Both the measured volume-based OP V DTT and OP V AA responses varied for the different extraction methods, since methanol extraction generated the lowest values and phosphate buffer the highest. Although all the tested solvents produced intercorrelated OP V DTT values, the phosphate buffer resulted the most useful for OP DTT assessment, as it provided the most sensible measure (nearly double values) compared with other extractions. The association of the measured OP V values with PM chemical composition suggested that oxidative properties of the investigated PM 2.5 samples depend on both transition metals and quinones, as also supported by additional experimental measurements on standard solutions of redox-active species.

Coating Lacticaseibacillus rhamnosus GG in Alginate Systems: an Emerging Strategy Towards Improved Viability in Orange Juice - Angela Bonaccorso; Nunziatina Russo; Alessia Romeo; Claudia Carbone; Maria Aurora Grimaudo; Carmen Alvarez-Lorenzo; Cinzia Randazzo; Teresa Musumeci; Cinzia Caggia (AAPS PharmSciTech, 2021)
Fruit juices are successfully proposed as suitable probiotic vehicles, but researchers’ efforts should be developed to avoid effects of bacteria overgrowing on sensory and nutritional cues of final products and to preserve viability of probiotic bacteria during storage. In the present study, encapsulation of Lacticaseibacillus rhamnosus GG strain in alginate systems was performed through ionotropic gelation technology. The alginate systems were optimized by using Box-Behnken Design to investigate the influence of three independent variables at three different levels: particle mean size and polydispersity index. The optimized probiotic-loaded alginate particles were added to orange juice samples. The viability of the probiotic strain, both as free and microencapsulated, was evaluated in orange juice stored at 5°C for 35 days. Morphology and size of probiotic-loaded alginate particles were found suitable for incorporation into juice. TEM analysis revealed that unloaded systems were clustered as nanoparticles (CL_NP), while the loaded sample appeared as a coated system (Coated_LGG). Microbiological evaluation revealed that the encapsulation assured the survival of Coated_LGG, with a reduction of less than 1-unit log in cellular density after 35 days of refrigerated storage in orange juice. Results indicated that the encapsulated bacteria did not affect the macroscopic properties neither the microbiological characteristic of orange juice; thus, it can be proposed as functional food.

Generation of hyperfunctional recombinant human factor IX variants expressed in human cell line SK-Hep-1 - Aline Sousa Bomfim; Marcela Cristina Corrêa de Freitas; Virgínia Picanço Castro; Mario Abreu Soares Neto; Ricardo Pádua; Dimas Tadeu Covas; Elisa Maria Sousa Russo (Biotechnology Letters, 2021)

ISSR markers to explore entomopathogenic fungi genetic diversity: Implications for biological control of tobacco pests - Maria Florencia Vianna; Sebastian Pelizza; María Leticia Russo; Andrea Toledo; Cecilia Mourelos; Ana Clara Scorsetti (Journal of Biosciences, 2020)

Exine morphometric analysis as a new tool for Citrus species identification: a case study from Oplontis (Vesuvius area, Italy) - Maria Rosaria Barone Lumaga; Elda Russo Ermolli; Bruno Menale; Stefano Vitale (Vegetation History and Archaeobotany, 2020)

Seismic networks layout optimization for a high-resolution monitoring of induced micro-seismicity - Grazia De Landro; Matteo Picozzi; Guido Russo; Guido Maria Adinolfi; Aldo Zollo (Journal of Seismology, 2020)

Calongea prieguensis (Pezizaceae), a rare hypogeous ascomycetes in Europe - Carmelo Arturo Buccheri; Antonino Fiocco; Mario Russo; Gianrico Vasquez; Giuseppe Venturella; Roberta Calvo; Maria Letizia Gargano (Plant Biosystems, 2020)

(−)-linalool-Loaded Polymeric Nanocapsules Are a Potential Candidate to Fibromyalgia Treatment - Tatianny de Araujo Andrade; Paula dos Passos Menezes; Yasmim Maria Barbosa Gomes de Carvalho; Bruno dos Santos Lima; Eloísa Portugal Barros Silva Soares de Souza; Adriano Antunes de Souza Araujo; Marlange Almeida Oliveira Melo; Lucindo José Quintans-Júnior; Jullyana de Souza Siqueira Quintans; Sílvia Stanisçuaski Guterres; Adriana Raffin Pohlmann; Saravanan Shanmugam; et al. (AAPS PharmSciTech, 2020)

Accumulation and Depuration Kinetics of Rotavirus in Mussels Experimentally Contaminated - Maria Grazia Amoroso; Antonio Luca Langellotti; Valeria Russo; Anna Martello; Marina Monini; Ilaria Di Bartolo; Giovanni Ianiro; Denise Di Concilio; Giorgio Galiero; Giovanna Fusco (Food and Environmental Virology, 2020)

Effects of Histone Deacetylase Inhibitors on the Development of Epilepsy and Psychiatric Comorbidity in WAG/Rij Rats - Rita Citraro; Antonio Leo; Carmen De Caro; Valentina Nesci; Maria E. Gallo Cantafio; Nicola Amodio; Giuseppina Mattace Raso; Adriano Lama; Roberto Russo; Antonio Calignano; Martina Tallarico; Emilio Russo; et al. (Molecular Neurobiology, 2020)

Wharton’s Jelly Mesenchymal Stromal Cells from Human Umbilical Cord: a Close-up on Immunomodulatory Molecules Featured In Situ and In Vitro - Tiziana Corsello; Giandomenico Amico; Simona Corrao; Rita Anzalone; Francesca Timoneri; Melania Lo Iacono; Eleonora Russo; Giovanni Francesco Spatola; Maria Laura Uzzo; Mario Giuffrè; Martin Caprnda; Peter Kubatka; et al. (Stem Cell Reviews and Reports, 2019)

Understanding fungal potential in the mitigation of contaminated areas in the Czech Republic: tolerance, biotransformation of hexachlorocyclohexane (HCH) and oxidative stress analysis - Fabiana Russo; Andrea Ceci; Oriana Maggi; Antonietta Siciliano; Marco Guida; Marco Petrangeli Papini; Miroslav Černík; Anna Maria Persiani (Environmental Science and Pollution Research, 2019)

Cross-amplification of nuclear microsatellite markers in Aechmea distichantha Lem. (Bromeliaceae) - Fernanda Maria de Russo Godoy; Gecele Matos Paggi; Clarisse Palma-Silva (Brazilian Journal of Botany, 2019)

Investigation of Enzymatic Hydrolysis of Coffee Silverskin Aimed at the Production of Butanol and Succinic Acid by Fermentative Processes - Saverio Niglio; Alessandra Procentese; Maria Elena Russo; Giovanni Sannia; Antonio Marzocchella (BioEnergy Research, 2019)

AutoTube: a novel software for the automated morphometric analysis of vascular networks in tissues - Javier A. Montoya-Zegarra; Erica Russo; Peter Runge; Maria Jadhav; Ann-Helen Willrodt; Szymon Stoma; Simon F. Nørrelykke; Michael Detmar; Cornelia Halin (Angiogenesis, 2019)

Chemical characterization of vines grown in incipient volcanic soils of Fogo Island (Cape Verde) - Rosa Marques; Maria Isabel Prudêncio; Maria Manuela Abreu; Dulce Russo; José G. Marques; Fernando Rocha (Environmental Monitoring and Assessment, 2019)

Evaluation of a commercial enzyme-linked immunosorbent assay (ELISA) for detecting antibodies against Toxoplasma gondii from naturally and experimentally infected pigs - Giusi Macaluso; Santina Di Bella; Giuseppa Purpari; Elisabetta Giudice; Francesco Mira; Francesca Gucciardi; Anna Maria Fausta Marino; Carmelo Russo; Maria Angeles Gómez-Morales; Annalisa Guercio (Infectious Diseases, 2019)

Ipsilateral somatosensory responses in humans: the tonic activity of SII and posterior insular cortex - Maria Del Vecchio; Fausto Caruana; Ivana Sartori; Veronica Pelliccia; Giorgio Lo Russo; Giacomo Rizzolatti; Pietro Avanzini (Brain Structure and Function, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Genome editing in diatoms: achievements and goals - Peter G. Kroth; Atle M. Bones; Fayza Daboussi; Maria I. Ferrante; Marianne Jaubert; Misha Kolot; Marianne Nymark; Carolina Río Bártulos; Andrés Ritter; Monia T. Russo; Manuel Serif; Per Winge; et al. (Plant Cell Reports, 2018)

Nrf2 targeting by sulforaphane: A potential therapy for cancer treatment - Maria Russo; Carmela Spagnuolo; Gian Luigi Russo; Krystyna Skalicka-Woźniak; Maria Daglia; Eduardo Sobarzo-Sánchez; Seyed Fazel Nabavi; Seyed Mohammad Nabavi (Critical Reviews in Food Science and Nutrition, 2018)

Mitochondrial mRNA expression in fibroblasts of Down syndrome subjects - Michele Salemi; Mariaconcetta Giambirtone; Concetta Barone; Maria Grazia Salluzzo; Roberto Russo; Mariangela Lo Giudice; Salvatore Cutuli; Federico Ridolfo; Corrado Romano (Human Cell, 2018)

Saprotrophic soil fungi to improve phosphorus solubilisation and release: In vitro abilities of several species - Andrea Ceci; Flavia Pinzari; Fabiana Russo; Oriana Maggi; Anna Maria Persiani (Ambio, 2018)

Anti-angiogenic activity and phytochemical screening of fruit fractions from Vitex agnus castus - Giovanna Certo; Rosaria Costa; Valeria D’Angelo; Marina Russo; Ambrogina Albergamo; Giacomo Dugo; Maria Paola Germanò (Natural Product Research, 2017)

Interplay between sea level rise and tectonics in the Holocene evolution of the St. Eufemia Plain (Calabria, Italy) - Maria Rosaria Ruello; Aldo Cinque; Valentino Di Donato; Flavia Molisso; Filippo Terrasi; Elda Russo Ermolli (Journal of Coastal Conservation, 2017)

Early onset brain calcifications secondary to hypoparathyroidism in a boy with syncopal-like symptomatology - Maria Grazia Pasca; Elisabetta Lucarelli; Luigi Russo; Isabella Fanizza; Antonio Trabacca (Acta Neurologica Belgica, 2017)

A Holistic Approach to Fishery Management: Evidence and Insights from a Central Mediterranean Case Study (Western Ionian Sea) - Tommaso Russo; Isabella Bitetto; Pierluigi Carbonara; Roberto Carlucci; Lorenzo D'Andrea; Maria T. Facchini; Giuseppe Lembo; Porzia Maiorano; Letizia Sion; Maria T. Spedicato; Angelo Tursi; Stefano Cataudella (Frontiers in Marine Science, 2017)

An enhanced random walk algorithm for delineation of head and neck cancers in PET studies - Alessandro Stefano; Salvatore Vitabile; Giorgio Russo; Massimo Ippolito; Maria Gabriella Sabini; Daniele Sardina; Orazio Gambino; Roberto Pirrone; Edoardo Ardizzone; Maria Carla Gilardi (Medical & Biological Engineering & Computing, 2017)

Site characterization of Italian accelerometric stations - Chiara Felicetta; Maria D’Amico; Giovanni Lanzano; Rodolfo Puglia; Emiliano Russo; Lucia Luzi (Bulletin of Earthquake Engineering, 2017)

Gas chromatography-tandem mass spectrometry multi-residual analysis of contaminants in Italian honey samples - Marcello Saitta; Giuseppa Di Bella; Maria Rita Fede; Vincenzo Lo Turco; Angela Giorgia Potortì; Rossana Rando; Maria Teresa Russo; Giacomo Dugo (Food Additives & Contaminants: Part A, 2017)

Molecular Modeling and Physicochemical Properties of Supramolecular Complexes of Limonene with α- and β-Cyclodextrins - Paula dos Passos Menezes; Polliana Barbosa Pereira dos Santos; Grace Anne Azevedo Dória; Bruna Maria Hipólito de Sousa; Mairim Russo Serafini; Paula Santos Nunes; Lucindo José Quintans-Júnior; Iara Lisboa de Matos; Péricles Barreto Alves; Daniel Pereira Bezerra; Francisco Jaime Bezerra Mendonça Júnior; Gabriel Francisco da Silva; et al. (AAPS PharmSciTech, 2017)

Cerebrotendinous xanthomatosis, a metabolic disease with different neurological signs: two case reports - Maria Donata Di Taranto; Monica Gelzo; Carola Giacobbe; Marco Gentile; Gennaro Marotta; Silvia Savastano; Antonio Dello Russo; Giuliana Fortunato; Gaetano Corso (Metabolic Brain Disease, 2016)

Cytokines in Machado Joseph Disease/Spinocerebellar Ataxia 3 - Gerson da Silva Carvalho; Jonas Alex Morales Saute; Clarissa Branco Haas; Vitor Rocco Torrez; Andressa Wigner Brochier; Gabriele Nunes Souza; Gabriel Vasata Furtado; Tailise Gheno; Aline Russo; Thais Lampert Monte; Artur Schumacher-Schuh; Rui D’Avila; et al. (The Cerebellum, 2016)

Combining split-and-merge and multi-seed region growing algorithms for uterine fibroid segmentation in MRgFUS treatments - Leonardo Rundo; Carmelo Militello; Salvatore Vitabile; Carlo Casarino; Giorgio Russo; Massimo Midiri; Maria Carla Gilardi (Medical & Biological Engineering & Computing, 2016)

Approaches for recombinant human factor IX production in serum-free suspension cultures - Robson Luis Ferraz do Amaral; Aline de Sousa Bomfim; Mário Soares de Abreu-Neto; Virgínia Picanço-Castro; Elisa Maria de Sousa Russo; Dimas Tadeu Covas; Kamilla Swiech (Biotechnology Letters, 2016)

Omega-3 polyunsaturated fatty acids and cancer: lessons learned from clinical trials - Seyed Fazel Nabavi; Stefania Bilotto; Gian Luigi Russo; Ilkay Erdogan Orhan; Solomon Habtemariam; Maria Daglia; Kasi Pandima Devi; Monica Rosa Loizzo; Rosa Tundis; Seyed Mohammad Nabavi (Cancer and Metastasis Reviews, 2015)

Establishment of Genetic Transformation in the Sexually Reproducing Diatoms Pseudo-nitzschia multistriata and Pseudo-nitzschia arenysensis and Inheritance of the Transgene - Valeria Sabatino; Monia Teresa Russo; Shrikant Patil; Giuliana d’Ippolito; Angelo Fontana; Maria Immacolata Ferrante (Marine Biotechnology, 2015)

Significant differences in integration sites of Moloney murine leukemia virus/Moloney murine sarcoma virus retroviral vector carrying recombinant coagulation factor IX in two human cell lines - Andrielle Castilho-Fernandes; Aparecida Maria Fontes; Kuruvilla Joseph Abraham; Marcela Cristina Corrêa de Freitas; Nathalia Gonsales da Rosa; Virginia Picanço-Castro; Elisa Maria de Sousa Russo-Carbolante; Dimas Tadeu Covas (Biotechnology Letters, 2015)

Oxidized derivative of docosahexaenoic acid preferentially inhibit cell proliferation in triple negative over luminal breast cancer cells - Thomas J. Pogash; Karam El-Bayoumy; Shantu Amin; Krishne Gowda; Ricardo López de Cicco; Maria Barton; Yanrong Su; Irma H. Russo; Julie A. Himmelberger; Michael Slifker; Andrea Manni; Jose Russo (In Vitro Cellular & Developmental Biology - Animal, 2015)

Analysis of rockfall risk on mountainside roads: evaluation of the effect of protection devices - Claudia Mignelli; Daniele Peila; Stefano Lo Russo; Sara Maria Ratto; Massimo Broccolato (Natural Hazards, 2014)

Rubella virus genotype 1G and echovirus 9 as etiologic agents of exanthematous diseases in Brazil: insights from phylogenetic analysis - Cristina Adelaide Figueiredo; Adriana Luchs; Denise Hage Russo; Rita de Cassia Compagnoli Carmona; Ana Maria Sardinha Afonso; Maria Isabel de Oliveira; Suely Pires Curti; José Cassio de Moraes; Cristiana M. Toscano; Flavia Helena Ciccone; Maria do Carmo Sampaio Tavares Timenetsky (Archives of Virology, 2014)

Spinocerebellar Ataxias in Brazil—Frequencies and Modulating Effects of Related Genes - Raphael Machado de Castilhos; Gabriel Vasata Furtado; Tailise Conte Gheno; Paola Schaeffer; Aline Russo; Orlando Barsottini; José Luiz Pedroso; Diego Z. Salarini; Fernando Regla Vargas; Maria Angélica de Faria Domingues d Lima; Clécio Godeiro; Luiz Carlos Santana-da-Silva; et al. (The Cerebellum, 2014)

Association between GSTP1, GSTM1 and GSTT1 polymorphisms involved in xenobiotic metabolism and head and neck cancer development - Anelise Russo; Pamela Risardi Francelin; Ana Lívia Silva Galbiatti; Luis Sérgio Raposo; José Victor Maníglia; Érika Cristina Pavarino; Eny Maria Goloni-Bertollo (Molecular Biology Reports, 2013)

A high-density consensus map of A and B wheat genomes - Daniela Marone; Giovanni Laidò; Agata Gadaleta; Pasqualina Colasuonno; Donatella B. M. Ficco; Angelica Giancaspro; Stefania Giove; Giosué Panio; Maria A. Russo; Pasquale De Vita; Luigi Cattivelli; Roberto Papa; et al. (Theoretical and Applied Genetics, 2012)

Erratum to: Body Mass Index is Inversely Correlated with the Expanded CAG Repeat Length in SCA3/MJD Patients - Jonas Alex Morales Saute; Andrew Chaves Feitosa da Silva; Gabriele Nunes Souza; Aline Dutra Russo; Karina Carvalho Donis; Leonardo Vedolin; Maria Luiza Saraiva-Pereira; Luis Valmor Cruz Portela; Laura Bannach Jardim (The Cerebellum, 2012)

Body Mass Index is Inversely Correlated with the Expanded CAG Repeat Length in SCA3/MJD Patients - Jonas Alex Morales Saute; Andrew Chaves Feitosa da Silva; Gabriele Nunes Souza; Aline Dutra Russo; Karina Carvalho Donis; Leonardo Vedolin; Maria Luiza Saraiva-Pereira; Luis Valmor Cruz Portela; Laura Bannach Jardim (The Cerebellum, 2012)

Characterization of wheat DArT markers: genetic and functional features - Daniela Marone; Giosuè Panio; Donatella B. M. Ficco; Maria A. Russo; Pasquale De Vita; Roberto Papa; Diego Rubiales; Luigi Cattivelli; Anna M. Mastrangelo (Molecular Genetics and Genomics, 2012)

SK-HEP cells and lentiviral vector for production of human recombinant factor VIII - Nathalia Gonsales da Rosa; Kamilla Swiech; Virgínia Picanço-Castro; Elisa Maria de Sousa Russo-Carbolante; Mario Abreu Soares Neto; Andrielle de Castilho-Fernandes; Vitor Marcel Faça; Aparecida Maria Fontes; Dimas Tadeu Covas (Biotechnology Letters, 2012)

Uptake of copper from plasma proteins in cells where expression of CTR1 has been modulated - Theodros Z. Kidane; Ramin Farhad; Kyoung Jin Lee; Abraham Santos; Eric Russo; Maria C. Linder (BioMetals, 2012)

Location and stability of a recombinant ovine prion protein in synthetic humic-like mineral complexes - Amaranta Pucci; Fabio Russo; Maria A. Rao; Liliana Gianfreda; Luca Calamai; Luigi P. D’Acqui (Biology and Fertility of Soils, 2012)

Evolution of the Sele River coastal plain (southern Italy) during the Late Quaternary by inland and offshore stratigraphical analyses - Pietro P. C. Aucelli; Vincenzo Amato; Francesca Budillon; Maria Rosaria Senatore; Sabrina Amodio; Carmine D’Amico; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Holocene environmental evolution of the costal sector in front of the Poseidonia-Paestum archaeological area (Sele plain, southern Italy) - Vincenzo Amato; Pietro Patrizio Ciro Aucelli; Bruno D’Argenio; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Paola Petrosino; Carmen Maria Rosskopf; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Polymorphisms of the CYP1A1 and CYP2E1 genes in head and neck squamous cell carcinoma risk - Nathália Moreno Cury; Anelise Russo; Ana Lívia Silva Galbiatti; Mariângela Torreglosa Ruiz; Luiz Sérgio Raposo; José Victor Maniglia; Érika Cristina Pavarino; Eny Maria Goloni-Bertollo (Molecular Biology Reports, 2012)

The peculiar heme pocket of the 2/2 hemoglobin of cold-adapted Pseudoalteromonas haloplanktis TAC125 - Barry D. Howes; Daniela Giordano; Leonardo Boechi; Roberta Russo; Simona Mucciacciaro; Chiara Ciaccio; Federica Sinibaldi; Maria Fittipaldi; Marcelo A. Martí; Darío A. Estrin; Guido di Prisco; Massimo Coletta; et al. (JBIC Journal of Biological Inorganic Chemistry, 2011)

Integration pattern of HIV-1 based lentiviral vector carrying recombinant coagulation factor VIII in Sk-Hep and 293T cells - Elisa Maria de Sousa Russo-Carbolante; Virgínia Picanço-Castro; Daiani Cristina Cilão Alves; Andrielle Castilho Fernandes; Graça Almeida-Porada; Torsten Tonn; Dimas Tadeu Covas (Biotechnology Letters, 2011)

Encapsulation of Ketoprofen and Ketoprofen Lysinate by Prilling for Controlled Drug Release - Pasquale Del Gaudio; Paola Russo; Maria Rosaria Lauro; Paolo Colombo; Rita P. Aquino (AAPS PharmSciTech, 2009)

Identification of differentially expressed genes in the flesh of blood and common oranges - Concetta Licciardello; Maria Patrizia Russo; Gianpiero Vale’; Reforgiato Giuseppe Recupero (Tree Genetics & Genomes, 2008)

The Effects of the Fungicide Methyl Thiophanate on Adrenal Gland Morphophysiology of the Lizard, Podarcis sicula - Maria De Falco; Rosaria Sciarrillo; Anna Capaldo; Tiziana Russo; Flaminia Gay; Salvatore Valiante; Lorenzo Varano; Vincenza Laforgia (Archives of Environmental Contamination and Toxicology, 2007)

Local administration of WIN 55,212-2 reduces chronic granuloma-associated angiogenesis in rat by inhibiting NF-κB activation - Daniele De Filippis; Annapina Russo; Daniela De Stefano; Maria Chiara Maiuri; Giuseppe Esposito; Maria Pia Cinelli; Concetta Pietropaolo; Rosa Carnuccio; Giulia Russo; Teresa Iuvone (Journal of Molecular Medicine, 2007)

Age-related alteration of 1α,25(OH)2-vitamin D3-dependent activation of p38 MAPK in rat intestinal cells - Verónica Gonzalez Pardo; Maria Marta Facchinetti; Alejandro Curino; Ricardo Boland; Ana Russo de Boland (Biogerontology, 2007)

NUCLEUS IMAGE PROPERTIES AND CELL DEATH IN MCF-10F CELLS GROWN ON SLIDE SUBSTRATES DIFFERING IN NATURE AND SIZE - MARIA LUIZA S. MELLO; M. H. LAREEF; A. B. SANTOS; J. RUSSO; B. C. VIDAL (In Vitro Cellular & Developmental Biology - Animal, 2005)

Nucleus image properties and cell death in MCF-10F cells grown on slide substrates differing in nature and size - Maria Luiza MELLO; Mohamed Lareef; Adriana Santos; Jose Russo; Benedicto Vidal (In Vitro Cellular & Developmental Biology - Animal, 2005)

Distribution of apelin, the endogenous ligand of the APJ receptor,in the lizard Podarcis sicula - Maria De Falco; Valentina Fedele; Tiziana Russo; Francesca Virgilio; Rosaria Sciarrillo; Stanislao Leone; Vincenza Laforgia; Antonio De Luca (Journal of Molecular Histology, 2004)

Specificity of Cellular Expression of C. variopedatus Polychaete Innexin in the Developing Embryo: Evolutionary Aspects of Innexins? Heterogeneous Gene Structures - Nicoletta Potenza; Rosanna del Gaudio; Maria Luisa Chiusano; Giuseppina Maria Rosaria Russo; Giuseppe Geraci (Journal of Molecular Evolution, 2003)

Endothelin-B (ET B ) receptor distribution in tissues of the lizard Podarcis sicula - Maria De Falco; Vincenza Laforgia; Valentina Fedele; Tiziana Russo; Luca De Luca; Giuliano Cottone; Lorenzo Varano; Antonio De Luca (Cell and Tissue Research, 2002)

Cytogenetic Mapping of Five YAC Clones to Human Chromosome Region 2q31 → q32.1 in Relation to the FRA2G Common Fragile Site - Franca Pelliccia; Maria Zaira Limongi; Lucia Gaddini; Maria Teresa Russo; Angela Rocchi (Genetica, 2002)

Cloning and Molecular Characterization of the First Innexin of the Phylum Annelida—Expression of the Gene During Development - Nicoletta Potenza; Rosanna del Gaudio; Loredana Rivieccio; Giuseppina Maria Rosaria Russo; Giuseppe Geraci (Journal of Molecular Evolution, 2002)

On the interrelationship between outdoor air pollution and respiratory allergy - Gennaro D'Amato; Gennaro Liccardi; Maria Russo; Maria D'Amato (Aerobiologia, 2000)

Apoptosis: identification by a critical electrolyte concentration method - B. C. Vidal; L. F. Barbisan; S. S. Maria; J. Russo; M. L. S. Mello (Apoptosis, 1996)

Clinical significance of allergic sensitization toOlea europaea L. pollen in Naples area, Italy - Gennaro Liccardi; Maria Russo; Maria Saggese; Gaetano Lobefalo; Paolo Noschese; Amedeo Piccolo; Antonella Visone; Maria D'Amato; Gennaro D'Amato (Aerobiologia, 1994)

Evaluation of the age of onset of respiratory allergic symptomatology - Gennaro Liccardi; Gaetano Lobefalo; Maria Russo; Andrea Manzi; Gennaro D'Amato (Aerobiologia, 1992)